Muito além do que se vê: a alegoria, em Ensaio sobre a cegueira, de José Saramago - Souza, Adriana Vieira de (2011)
The objective of this research is the analysis of textual features worked by José Saramago, the allegorical structure of his novel Ensaio sobre a cegueira (1995). It presents a review of the theoretical concept of allegory, considering its origins, forms and subdivisions, and points out the similarities and the imbalance between allegory and other figures of speech. This sort of historical allegory: "allegory of poets" and "allegory of theologians." It highlights the opposition between symbol and allegory, promoted by the romantics and focuses on the concept of "allegorical reading." It points to the allegorical elements present in the narrative: the words that illustrate his own title, the intertextuality with the sayings, the characters, the narrator and narrative spaces. Based on studies of Walter Benjamin, Kothe Flávio, João Adolfo Hansen, Mikhail Bakhtin and Marc Augé, seeks to highlight the novel by Saramago as a place for questioning the man in the world.